Genotype Frequency of Cytochrome P450 2C9 (CYP2C9) Mutations in Iraqi Ethnic Groups - Suhad R. AL- Tayie; Salwa Jaber Al-Awadi; Iqbal harbi Mohammed Al-Zaidi (Indian Journal of Forensic Medicine & Toxicology, 2021)
In Middle East, There is a little knowledge about the cytochrome P450s genotyping and there has not foundany investigation about the CYP2C9 allelic diversity in Iraqi population nowadays .CYP2C9 genotypes wereestablished in a total of 400 subjects of healthy Iraqis volunteers from different areas in Iraq (Arab ,Kurdand Turkmen). After extraction of DNA from blood cells and polymerase chain reaction, SNP genotypingfor CYP2C9 variants (2,3,4 and 5) was performed by using the primer extension KASP® genotyping assay.The agreement with “Hardy-Weinberg equilibrium” for detected the distribution of CYP2C9 genotypewas proved by (X2 – test) .The CYP2C9*2 , CYP2C9*3 and CYP2C9*5 alleles variant were identified inIraqi population , whereas the CYP2C9*4 was absent , The results revealed that there was non- significantassociation observed in all CYP2C9 genotypes among Iraqi ethnic groups .then The CYP2C9 genotypesresults in our study were compared to other populations and The results exhibited that the frequency of Iraqipopulation CYP2C9 variants were comparable with other countries and ethnic groups. This is the first reportof CYP2C9 variants from Iraq; the results are assist as a database on CYP2C9 gene polymorphisms andclinical data baseline for dosing and avoiding adverse reactions of drugs metabolized by CYP2C9 in Iraqispatients.